Croce e la questione dell’origine del linguaggio - Giuliani, Fabrizia (Aesthetica Preprint, 2024)
The problem of the origin and evolution of language plays a crucial role in current research, which continues to regard it as “the most difficult problem,” if not a mystery. Throughout history, the centrality of this theme has remained undiminished, even if not always fully recognized. In this essay, we will explore Crocean philosophy, where this theme holds significant importance despite encountering misunderstandings. We will trace the evolution of the question of language’s origin from the Tesi to the latest developments in Hegelian philosophy, while also comparing Croce’s dialogues with authors from both the past and present—from Vico and Humboldt to De Martino. A framework emerges illustrating how interpretive misunderstandings often arise from perspectives associated with current research paradigms, particularly structuralism. In recent years, some of Croce’s assertions, starting with the alignment of the theme of origin with its essence, have regained a central position. This does not imply an improbable relevance of Croce’s thought, but rather underscores the necessity of directly observing how theoretical hypotheses take shape within their contexts to fortify the foundations of the emerging alternatives today.